The Roles of Lpar1 in Central Nervous System Disorders and Diseases - Xiao, Dongqiong; Su, Xiaojuan; Gao, Hu; Li, Xihong; Qu, Yi (Frontiers in Neuroscience, 2021)
Lysophosphatidic acid receptor 1 (Lpar1), which is found in almost all human tissues but is most abundant in the brain, can couple to G protein-coupled receptors (GPCRs) and participate in regulating cell proliferation, migration, survival, and apoptosis. Edg2, the protein encoded by the Lpar1 gene, is present on various cell types in the central nervous system (CNS), such as neural stem cells (NSCs), oligodendrocytes, neurons, astrocytes, and microglia. Lpar1 deletion causes neurodevelopmental disorders and CNS diseases, such as brain cancer, neuropsychiatric disorders, demyelination diseases, and neuropathic pain. Here, we summarize the possible roles and mechanisms of Lpar1/Edg2 in CNS disorders and diseases and propose that Lpar1/Edg2 might be a potential therapeutic target for CNS disorders and diseases.